Efeito da infecção por Trypanosoma vivax sobre a ingestão de alimento, conversão alimentar, ganho de peso e características da carcaça de ovinos infectados experimentalmente - Brito, Parmênedes Dias de (Universidade Federal Rural do Semi-Árido, 2011)
Trypanosomiasis caused by Trypanosoma vivax, is a debilitating and often fatal disease in domestic animals, which causes economic losses to cause growth retardation, abortion, decreased productivity, high costs of treatment and even death of the severely affected animals. This study aims avaluate the changes caused by T. vivax on performance and carcass characteristics of sheep, with no racial pattern defined experimentally infected in Mossoró, Rio Grande do Norte, Brazil. We used 10 ovines, male, without defined racial standard (WDRS), adults of average weight 20 kg, during the finishing stage, arranged in two treatments: control group and the group infected with strain of T. vivax originating from the outbreak of Paraíba with inoculum of 1,3 x 105 viable tripomastigostas. The animals were kept in two in sheds covered for 70 days in the same management conditions and feeding. Clinical symptoms, temperature and parasitemia were monitored daily. Weekly blood tests were performed, serum biochemistry, evaluation of feed intake and weight measurements, and calculation of feed efficiency ratio and feed every 15 days. At the end of the experiment, was the sacrifice of animals for evaluation of performance and carcass traits. There was a negative effect of T. vivax in feed conversion and feed efficiency ratio (P <0.05). The average weekly weight gain of the infected group was always lower when compared to the control group. Inherent in the feed intake was observed that there was no difference (P> 0.05) in total feed consumed weekly. Only the beef ribs and ham cuts showed a significant difference (P <0.05). But it is noteworthy that the infected group showed weight of the palette, neck, back and saw, 9%, 16%, 24% and 25% lower compared to the control group. There was a negative effect on fat deposition surface (P <0.05) and longissimus muscle area (P <0.05). Trypanosomiasis caused by T. vivax can cause direct losses in animal performance of 19,72% and resulting in economic losses for rural producers of up to 45,86% when deaths occur in the herd
Effect of Trypanosoma vivax infection on feed intake, feed conversion, weight gain and carcass characteristics of sheep experimentally infected
Keywords: Ovines; Tripanossomiases; Trypanosoma vivax; Yield carcass; Ovinos; Tripanossomíase; Trypanosoma vivax; Rendimento de carcaça; CIENCIAS AGRARIAS::MEDICINA VETERINARIA